"Dubbing" precolonial Africa and the Atlantic diaspora: Historical knowledge and the Global South: O Comércio de Marfim no Mundo Atlântico: Circulação e Produção (Séculos XV a XIX), edited by Silva Santos, Vanicléia, Eduardo França Pavia and René Lommez Gomes, Belo Horizonte: Clio Gestão e Editora/Centro de Estudos Africanos da UFMG, 2017, 306 pp., R$89, ISBN: 978-8568158173. Issue 2 (2nd April 2020) - Green, Toby
ABSTRACT: What has passed for historical "knowledge" about precolonial Africa and the diaspora has for centuries been "dubbed" through the lens of foreign observers. The main research findings have been shaped by the concerns of external financial backers, be they the Portuguese crown and Missionary orders in the sixteenth and seventeenth centuries or the colonial governments of the twentieth century. This pattern has continued into the twenty-first century. Structural Adjustment Programmes made it almost impossible for African institutions to focus on precolonial knowledge paradigms, and the process of knowledge production in this field was captured by the Global North. As the works considered in this review show, this pattern began to change with the growth of African Studies in Brazil. This review article considers the impact of these works, the different lens which they offer for precolonial Africa, and the consequences this may have for current debates on decolonizing the curriculum.